Working memory arrest in children with high-functioning autism compared to children with attention-deficit/hyperactivity disorder: Results from a 2-year longitudinal study. (May 2015) - Andersen, Per N; Skogli, Erik W; Hovik, Kjell T; Geurts, Hilde; Egeland, Jens; Øie, Merete
The aim of this study was to analyse the development of verbal working memory in children with high-functioning autism compared to children with attention-deficit/hyperactivity disorder and typically developing children. A total of 34 children with high-functioning autism, 72 children with attention-deficit/hyperactivity disorder and 45 typically developing children (age 9–16 years) were included at baseline and followed up approximately 25 months later. The children were given a letter/number sequencing task to assess verbal working memory. The performance of children with high-functioning autism on verbal working memory did not improve after 2 years, while improvement was observed in children with attention-deficit/hyperactivity disorder and typically developing children. The results indicate a different developmental trajectory for verbal working memory in children with high-functioning autism compared to children with attention-deficit/hyperactivity disorder and typically developing children. More research is needed to construct a developmental framework more suitable for children with autism spectrum disorder.